Balto-Slavic accentology, Auslautgesetze, and the Baltic secondary local cases - Villanueva Svensson, Miguel (Baltistica, 2020)
The article discusses the history of the Baltic secondary local cases within the framework of modern Balto-Slavic accentology and recent advances in our knowledge of the Baltic Auslautgesetze. The main factor determining the accent of the local cases was the development of Balto-Slavic enclinomena in Baltic. When the local cases were created enclinomena were still preserved, leading to word forms with stress on the original adposition (e.g. o-stem all. sg. *miśkā+pr̲̲). When nominal enclinomena were lost the accent shifted to the immediate left with concomitant métatonie rude, yielding *miśkā̲̍pre̲̲ (Lith. miškóp(i), in contrast with gen. sg. mìško). This was the origin of unexpected stress position and unexpected acute intonation in the secondary local cases. Another important factor was Saussure’s law, which took place at a much later stage in the immediate prehistory of Lithuanian. Other conclusions emanating from the accentological approach of this article include the following: 1) the illative, allative and adessive go back to Proto-Baltic and reflect Uralic influence. The inessive was created in East Baltic; 2) the adessive was built on the dative, as first proposed by Rosinas (2000); 3) the local cases underwent a number of innovations in East Baltic, most saliently in the illative plural and the locative; 4) the adpositional nature of the allative and adessive was perceived for a considerably longer period of time than that of the illative and inessive, which determined a partly different development of these cases; 5) finally, new accounts are proposed for some of the local cases (i- and u-stem dative and adessive singular; ā- and ē-stem locative and inessive singular; u-stem inessive singular; illative plural).